2016
DOI: 10.1097/sla.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Procalcitonin and C-reactive Protein for the Early Diagnosis of Intra-abdominal Infection After Elective Colorectal Surgery

Abstract: Levels of inflammatory markers under the cutoff value between postoperative days 3 and 5 ensure safe early discharge after elective colorectal surgery. Procalcitonin seems not to have added value as compared to C-reactive protein in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 41 publications
5
68
1
5
Order By: Relevance
“…The dynamics of postoperative Procalcitonin (PCT) are slightly different to those of CRP, with similar findings as in our study (14,34). Early elevation of measurable PCT (on the first or second postoperative days, for example), will be non-specific and reflect bacterial contamination or translocation secondary to bowel preparation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The dynamics of postoperative Procalcitonin (PCT) are slightly different to those of CRP, with similar findings as in our study (14,34). Early elevation of measurable PCT (on the first or second postoperative days, for example), will be non-specific and reflect bacterial contamination or translocation secondary to bowel preparation.…”
Section: Discussionsupporting
confidence: 79%
“…An almost identical level of CRP and its postoperative timing and sensitivity for the diagnosis of AL was recently reported by Scepanovic et al (33). Several studies have compared CRP at different time points following colorectal surgery (12) where Cousin et al (34) found a greater discrimination with CRP for AL diagnosis by the 5th postoperative day. Such timing might be too late, however, for surgical teams, which discharge their patients earlier than this time point as part of their policy of REfEREnCES:…”
Section: Discussionsupporting
confidence: 56%
“…Although the negative predictive value was found to be high, which may help to ensure early discharge [57], the specificity was quite low. Also, a meta-analysis including 2692 patients after colorectal surgery showed no advantage of PCT compared to CRP regarding diagnostic accuracy and mortality prediction [58]. This was confirmed recently in a similar large prospective study including 501 patients [59].…”
Section: Introductionmentioning
confidence: 76%
“…19 Table 2 describes additional information regarding the sensitivity and specificity of PCT in aiding in the diagnosis of a variety of disease states. [20][21][22][23][24][25][26][27][28][29][30][31] In addition to contributing to accurate diagnoses, PCT levels were shown to correlate with the extent and severity of microbial invasion, with higher PCT levels indicative of poorer prognosis. 32,33 PCT levels greater than 1 ng/ml at any point during a study of 427 patients hospitalized in the ICU were associated with increased mortality.…”
Section: Evidence For Procalcitonin As a Diagnostic And Prognostic Dementioning
confidence: 99%